Synthesis and characterization of alkanolamide polyols for rigid polyurethane foams as potential thermal insulation materials - Kamairudin, Norsuhaili (2024)
Hydroxyl compounds currently used in the production of polyurethane foam (PUF) are petrochemical products. However, they are non-renewable resources and may cause environmental pollution, and maybe exhausted in the near future. Thus, the availability of methyl oleate (MO) derived from palm oil provides an excellent feedstock to produce bio-polyol for polyurethane applications. The main objective is to investigate rigid polyurethane foams (RPUFs) prepared from MO are potential for thermal insulating material. Firstly, MO underwent epoxidation reaction and produced epoxidized methyl oleate (EMO) with the oxirane oxygen content (OOC) of 5.10%. Then, EMO was further subjected to two types of epoxide ring-opening reaction, namely epoxide ring-opening reaction with glycerol and oligomerization reaction of EMO in solvent. For epoxide ring-opening reaction with glycerol, the reaction conditions were optimized in order to obtain the maximum hydroxyl value (OHV) of bio-polyol, denoted as MOG-polyol, giving the highest OHV of 306 mg KOH/g. For the oligomerization reaction of EMO in solvent, the highest OHV obtained was 166 mg KOH/g and denoted as OMOP-polyol. These two bio-polyols then undergo amidation reaction to increase OHV and produced alkanolamide polyols. The optimum reaction conditions for amidation reaction of MOG-polyol were 1:2 mole ratio of (MOG-polyol: DEA) with catalyst loading of 0.25% over 3hrs reaction at 120 °C, giving the highest OHV of alkanoamide polyol, denoted as MOAG-polyol of 313 mg KOH/g. The similar reaction conditions were used in order to synthesis alkanolamide polyol denoted as OMOAP-polyol from OMOP-polyol where the OHV obtained was 282 mg KOH/g. Both alkanolamide polyols were used as polyols for the production of RPUFs. RPUFs prepared from both of the alkanolamide polyols showed higher reactivity compared to the references foam which prepared from 100% of petroleum-based polyol due to its higher viscosity. RPUFs containing alkanolamide polyol also have higher apparent density (27.20-34.40 kg/m3) and compressive strength (141-180 kPa) compared to the reference foams. Reference foam have largest cell size compared to the RPUFs that were modified with alkanolamide polyols. Thermal conductivity is closely correlated with closed cell content. Higher thermal conductivity was found in RPUFs due to lower closed cell content. However, the thermal conductivities of RPFUs are still within the range for thermal insulating materials (<0.1 W/mK). Thus, the RPUFs made from alkanolamide polyols are potential candidate to be used as thermal insulation for refrigerator or freezers.